2015
DOI: 10.1080/15384047.2015.1078028
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of pyrrolo-1,5-benzoxazepine-15 and its synergistic effect with Oxaliplatin and 5-FU in colorectal cancer cells

Abstract: Some compounds of a series of novel pyrrolo-1,5-benzoxa(thia)zepine, a well-known group of tubulin targeting agents, display anti-tumor effects mainly inducing cell cycle arrest and apoptosis in several human cancer models. A member of this family, pyrrolo-1,5-benzoxazepine-15 (PBOX-15), has previously shown potent pro-apoptotic activity in a variety of human tumor cell types, with minimal toxicity toward normal blood and bone marrow cells. In this study, we evaluated the PBOX-15-mediated effects in human colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Therefore, new anti-CRC agents are still required. Previous research indicated that a tubulin-targeting agent, pyrrolo-1,5-benzoxazepine-15, had antitumor effects in CRC cell lines [18]. We found that 0.1 ”mol/L MPT0B002 and 2 ”mol/L MPT0B169 had similar effects on apoptotic induction (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Therefore, new anti-CRC agents are still required. Previous research indicated that a tubulin-targeting agent, pyrrolo-1,5-benzoxazepine-15, had antitumor effects in CRC cell lines [18]. We found that 0.1 ”mol/L MPT0B002 and 2 ”mol/L MPT0B169 had similar effects on apoptotic induction (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…All reagents for cell culture, N6-isopentenyladenosine (IPA), 5-fluorouracil (5-FU) and MG132 inhibitor (dissolved in DMSO) were purchased from Sigma–Aldrich (St. Louis, MO, USA). Cell proliferation was evaluated through BrdU incorporation measurement, through a colorimetric ELISA kit (Roche Diagnostics GmbH, Mannheim, Germany), as previously described [54]. All experiments were performed in triplicate, and the relative cell proliferation was expressed as a fold change versus untreated control cells.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, pyrrolo-1,5-benzoxazepine-15 (PBOX-15) (from 0.001 to 5 ”M), a synthetic inhibitor of FAAH, demonstrated a strong antiproliferative and proapoptotic effect in CRC cell lines. Moreover, it was observed that nanomolar concentration of PBOX-15 increased the anticancer action of 5-fluouracil (5-FU) [46].…”
Section: Gastrointestinal Cancersmentioning
confidence: 99%